2018
DOI: 10.19027/jai.17.2.130-136
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic nitrogen absorption in the aquaponics farming of sangkuriang catfish (Clarias gariepinus) at uneven retention periods

Abstract: <p align="center"><strong>Abstract</strong><strong></strong></p><p>Aquaponics is new aquaculture integrating the technology of fishes and plants due to less availability of land. This study aimed to determine the optimum retention period in the aquaponics farming of sangkuriang catfish (<em>Clarias gariepinus</em>) integrated with water spinach (<em>Ipomoea reptan</em>) to generate the water to support the catfish production. This study conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…This condition followed the study results of Kamauddin et al (2019) who stated that the use of cocopeat as a physical filter was insufficient to be utilized for water treatment in aquaponic system. The capability of water spinach as a good biological filter for catfish in aquaponic system was strengthened by the study results of Zahidah et al (2018) and Nazlia and Zulfiadi (2018). Zahidah et al (2018) stated that the combination of catfish and water spinach in an aquaponic system produced the best absolute growth rate at 7.8 ± 1.18 g. Meanwhile, the study results of Nazlia and Zulfiadi (2018) showed the highest survival rate and absolute growth rate of catfish in aquaponic system were obtained from the water spinach treatment, namely at 86.7% and 1.97 g, respectively.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This condition followed the study results of Kamauddin et al (2019) who stated that the use of cocopeat as a physical filter was insufficient to be utilized for water treatment in aquaponic system. The capability of water spinach as a good biological filter for catfish in aquaponic system was strengthened by the study results of Zahidah et al (2018) and Nazlia and Zulfiadi (2018). Zahidah et al (2018) stated that the combination of catfish and water spinach in an aquaponic system produced the best absolute growth rate at 7.8 ± 1.18 g. Meanwhile, the study results of Nazlia and Zulfiadi (2018) showed the highest survival rate and absolute growth rate of catfish in aquaponic system were obtained from the water spinach treatment, namely at 86.7% and 1.97 g, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…The capability of water spinach as a good biological filter for catfish in aquaponic system was strengthened by the study results of Zahidah et al (2018) and Nazlia and Zulfiadi (2018). Zahidah et al (2018) stated that the combination of catfish and water spinach in an aquaponic system produced the best absolute growth rate at 7.8 ± 1.18 g. Meanwhile, the study results of Nazlia and Zulfiadi (2018) showed the highest survival rate and absolute growth rate of catfish in aquaponic system were obtained from the water spinach treatment, namely at 86.7% and 1.97 g, respectively. According to Setijaningsih and Suryaningrum (2015), water spinach is more effective to utilize nutrients in the flowing water from the catfish maintenance tank.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Catfish [Clarias gariepinus (Burchell, 1822)] is a very popular commodity for cultivation in Africa, Indonesia, and several other countries in the world because of its fast growth, disease resistance, and wide geographical spread (Elesho et al, 2021). Consequently, catfish production in Indonesia has increased rapidly, accounting for 55 691 t in 2004 and climbed dramatically in 2014, reached 543 774 t (Zahidah et al, 2018). In addition, catfish production from 2017 to 2018 increased from 841.75 × 10 3 t to 1.81 × 10 6 t (114.82 %) (FAO, 2018).…”
Section: Introductionmentioning
confidence: 99%